2019
DOI: 10.1002/adma.201901965
|View full text |Cite
|
Sign up to set email alerts
|

An All‐Organic Semiconductor C3N4/PDINH Heterostructure with Advanced Antibacterial Photocatalytic Therapy Activity

Abstract: Antibacterial photocatalytic therapy has been reported as a promising alternative water disinfection technology for combating antibiotic‐resistant bacteria. Numerous inorganic nanosystems have been developed as antibiotic replacements for bacterial infection treatment, but these are limited due to the toxicity risk of heavy metal species. Organic semiconductor photocatalytic materials have attracted great attention due to their good biocompatibility, chemically tunable electronic structure, diverse structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(154 citation statements)
references
References 39 publications
4
144
0
Order By: Relevance
“…[6][7][8][9] In fact, numerous kinds of antibacterial materials and strategies have been developed in the past decades. For example, chemotherapies using antibacterial polypeptides, 10 noble metal nanoparticles (NPs), 11,12 semiconductor NPs 13,14 and carbon-based nanomaterials (CNMs) 15,16 were all proved to exhibit antimicrobial activities. More recently, photothermal or photodynamic sterilization techniques were extensively investigated in the eradication of bacteria via production of massive heating or the generation of reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In fact, numerous kinds of antibacterial materials and strategies have been developed in the past decades. For example, chemotherapies using antibacterial polypeptides, 10 noble metal nanoparticles (NPs), 11,12 semiconductor NPs 13,14 and carbon-based nanomaterials (CNMs) 15,16 were all proved to exhibit antimicrobial activities. More recently, photothermal or photodynamic sterilization techniques were extensively investigated in the eradication of bacteria via production of massive heating or the generation of reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Wang et al reported that vanadate quantum dots-inset g-C 3 N 4 (vanadate QDs/g-C 3 N 4 ) nanosheets showed faster photocatalytic disinfection with abundant ROS compared to bare g-C 3 N 4 nanosheets 171. Moreover, to reduce the toxicity risk of heavy metal species, Chen's groups created a novel all-organic self-assembled semiconductor photocatalytic nanomaterial C 3 N 4 /PDINH heterostructure for photocatalytic antibacterial by recrystallization of PDINH (perylene-3,4,9,10-tetracarboxylic diimide) on the surface of C 3 N 4 nanosheets in situ 201. Intriguingly, they found that the absorption spectrum of heterostructure were greatly extended from UV to NIR, enhancing the photocatalytic effect to generate more ROS for better bactericidal, while revealing low-toxicity to healthy tissue cells.…”
Section: 2d Nbg Antibacterial Nanomaterialsmentioning
confidence: 99%
“…2D metal‐free materials had been reported for photoinduced antibacterial behavior, but the photoinduced antibacterial efficiency is still far from practical applications. Recently, 2D organic semiconductor photoinduced antibacterial materials have attracted extensive attention due to their advantages such as good stability, low cost, chemically adjustable electrons, good biocompatibility, high carrier mobility, suitable bandgap, abundant element resources, and high electron affinity . This provides a new idea for the application of organic photoinduced antibacterial semiconductor in water sterilization.…”
Section: Antimicrobialmentioning
confidence: 99%